Alternative assembly processes from trait-mediated co-evolution in mutualistic communities. (7th October 2018) - Minoarivelo, Henintsoa O.; Hui, Cang
Highlights: Two alternative regimes result from the eco-evolutionary dynamics of mutualism. Species optimize the use of either intraguild resources or mutualistic benefits. Adaptive diversification is mainly driven by competition. Mutualism constrains adaptive diversification but enhances species abundance and maintains biodiversity. Abstract: Ecological and evolutionary dynamics observed in mutualistic communities can be shaped by several mechanisms, including ecological interactions and their co-evolutionary consequences. Here we explore how intra and interspecific competition, together with mutualistic interactions, can affect community assembly through their effects on adaptive diversification and the emergence of biodiversity. To capture both ecological and evolutionary processes simultaneously, we used the adaptive dynamics approach based on a Lotka-Volterra framework and simulated the ecological dynamics of populations as well as the evolutionary dynamics of phenotypic traits. Depending on the initial trait values, two possible alternative evolutionary regimes emerged: traits evolve towards either optimal utilization of environmental resources or maximizing the benefits from mutualistic interactions. Diversification and overall biodiversity are mostly driven by frequency-dependent competition, while mutualism plays an important role in enhancing ecosystem productivity and evolutionary stability. Because different initial trait values in a community can lead to alternative evolutionary regimes, species loss and biological invasions could not only alter ecological dynamics but also push the system onto an alternative successional climax or evolutionary end point. It thus becomes essential to clarify the past evolutionary dynamics so as to draw conclusions on key community assembly processes.